2004
DOI: 10.1111/j.1600-0668.2004.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Human response to personalized ventilation and mixing ventilation

Abstract: Personalized ventilation can improve occupants' thermal comfort, perceived air quality and decrease the intensity of SBS symptoms compared to mixing ventilation. Occupants will use the provided individual control of airflow rate and positioning of the air terminal device to obtain preferred microenvironment in rooms where the air temperature is within the range recommended by indoor climate standards. Development of more efficient air terminal devices is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
95
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(98 citation statements)
references
References 9 publications
1
95
0
2
Order By: Relevance
“…Studies have also revealed that Sick Building Syndrome (SBS) symptoms (headache, dizziness, etc.) decrease when PV is used, suggesting an improvement of occupants' health [4] in comparison to rooms with traditional mixing ventilation. Indication of improved occupant performance with PV was reported in rooms at 26 C [4].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies have also revealed that Sick Building Syndrome (SBS) symptoms (headache, dizziness, etc.) decrease when PV is used, suggesting an improvement of occupants' health [4] in comparison to rooms with traditional mixing ventilation. Indication of improved occupant performance with PV was reported in rooms at 26 C [4].…”
Section: Introductionmentioning
confidence: 89%
“…Measurements have shown that PV when properly designed can provide up to 100% clean air for inhalation [2,3]. Human subject experiments performed under laboratory conditions have documented the potential of PV for improvement of occupants' thermal comfort and perceived air quality (PAQ) [4,5]. Studies have also revealed that Sick Building Syndrome (SBS) symptoms (headache, dizziness, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This conventional PVS can provide individual control of inlet air temperature, airflow rate and direction. Different types of PVS with one air terminal device have been studied, e.g., [2][3][4][5][6][7][8][9]. In Cermark et al the measurements at the breathing zone with PVS were made [2], and in Melikov et al the evaluation of different types of PVS air terminal devices were analyzed [3].…”
Section: Introductionmentioning
confidence: 99%
“…In Cermark et al the measurements at the breathing zone with PVS were made [2], and in Melikov et al the evaluation of different types of PVS air terminal devices were analyzed [3]. The environment around human body with PVS was studied using CFD [4], the human thermal response to PVS and mixing ventilation system was applied in [5], the modeling the performance of PVS in several conditions in a room was analyzed in [6] and the conjunction of PVS with mixing ventilation system and displacement ventilation system was studied in [7]. In Niu et al the study using experimental techniques on a chair-based PVS was developed [8], and in Sun et al the personalized dynamic ventilation was analyzed [9].…”
Section: Introductionmentioning
confidence: 99%
“…Melikov and Fanger [4]- [6] have systematic reviews on the performance of personalized ventilation (PV) and on human response to it. PV, in comparison with traditional ventilation, has two important advantages: (i) it has potential for improving the inhaled air quality, and (ii) each occupant is delegated the authority to optimize as well as control the temperature, the flow rate, and the direction of supplied air according to their own preferences and to thermal comfort requirements.…”
Section: Introductionmentioning
confidence: 99%